2013
DOI: 10.5935/1808-8694.20130105
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of signs and symptoms of laryngopharyngeal reflux in snorers with suspected obstructive sleep apnea

Abstract: The significant difference seen in the prevalence of signs of inflammation suggestive of LPR when obese and non-obese subjects with suspected OSA were compared indicates that obesity may affect inflammatory findings of the pharynx and larynx. The high prevalence of symptoms and signs of reflux in patients with suspected OSA calls for more studies on the matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
4
17
1
3
Order By: Relevance
“…A number of recent studies have investigated the prevalence of reflux in OSA patients but in almost all cases this was done using clinical questionnaires alone [9,10,11,12,13,14,15,16,17]. These aspects emerged in a recent meta-analysis of the international literature, which analyzed the incidence of LPR in OSA patients [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have investigated the prevalence of reflux in OSA patients but in almost all cases this was done using clinical questionnaires alone [9,10,11,12,13,14,15,16,17]. These aspects emerged in a recent meta-analysis of the international literature, which analyzed the incidence of LPR in OSA patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, various studies have been published dealing with the correlation between laryngopharyngeal reflux (LPR) and OSA [9,10,11,12,13,14,15,16,17]. Although a high incidence of LPR in this class of patients has been reported [9,10,11,12,13,14,15,16,17], the possibility of a correlation between the severity of the pathology (number of hypopnea/apnea episodes) and LPR has not yet been clearly demonstrated [10,11,12,13,14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have noted coexistence between OSA and chronic cough or LPR. However, these studies have shown conflicting results, have been small and retrospective, or relied on extrapolation from treatment effects via continuous positive airway pressure (CPAP) or surgery without addressing initial prevalence. There is no prospective study examining the link between OSA and the severity of symptoms of chronic cough and LPR.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies with small sample sizes or retrospective design have shown a high prevalence of LPR and cough symptoms among patients with OSA. [28][29][30] Our prior report, with a smaller sample size (n = 52), found that the symptoms of chronic cough and LPR as measured by the LCQ and RSI, respectively, were worse among those with OSA. 34 In this study, we demonstrate this prior finding holds with a larger sample size.…”
Section: Discussionmentioning
confidence: 93%
“…There are previous studies that have investigated associations between laryngopharyngeal reflux (LPR) or chronic cough and OSA, but until a recent study by our group, there had been no prospective analysis of this association. [28][29][30][31][32][33] In our previous study, we analyzed data from the initial 52 patients of the cohort we currently report on and found that chronic cough, as measured by the Leicester Cough Questionnaire (LCQ), and LPR symptoms, as measured by the Reflux Symptom Index (RSI), were significantly more common among patients with OSA. 34 In this study, we expanded the sample size to assess the stability of our conclusions and use this better-powered sample to evaluate the value of the prepolysomnogram RSI in predicting OSA status.…”
Section: Introductionmentioning
confidence: 99%